The inspiring leader unlocking the secrets of how extraordinary leaders motivate - Zenger, John. (New York McGraw Hill, 2009)
In their bestselling work The Extraordinary Leader, performance thought leaders John Zenger and Joseph Folkman revealed the 16 key competencies that separate the top 10 percent of leaders from the rest. Since that book?s publication, they and coauthor Scott Edinger discovered, through an extensive study conducted over four years, that leaders who possessed the ability to inspire and motivate outperformed all others.
Includes bibliographical references (p. 235-238) and index.
Keywords: Leadership